Motivation, Mentorship, and Peer Role among Indonesian Students in Creative Literature Projects: An Exploration of Problem-Solving Abilitiess - Sari, Harmita; Aco, Dedi; Liu , Ming Chou; Anshari; Halim, Abdul (OKARA: Jurnal Bahasa dan Sastra, 2025)
Despite the recognized benefits of creative project-based learning, research on problem-solving abilities remains largely focused on STEM disciplines, leaving a significant gap in the humanities. Furthermore, how motivation, mentorship, and peer dynamics collectively interact to drive creative problem-solving within the Indonesian educational context remains underexplored. To address this, this study investigates the impact of these psychosocial factors on students’ problem-solving abilities during creative literature projects. Using structural equation modeling (SEM), we analyzed survey data from 100 elementary and junior high school students in Indonesia who actively participated in university-collaborated literature programs. The model evaluated motivation, mentorship, and peer relationships as independent variables; problem-solving abilities as a mediator; and project outcomes as the dependent variable. The findings reveal that motivation and mentorship significantly enhance problem-solving abilities, whereas peer relationships exert a comparatively lesser influence. Crucially, problem-solving abilities fully mediate the relationship between these psychosocial inputs and final project outcomes. In practice, educators should prioritize cultivating intrinsic motivation and active mentorship to enhance the success of creative problem-solving. Future research should explore these dynamics globally using a multi-level approach.